(NuKRA)QÇNKI W ÆSTORÆÇ (B/s)E - (NbORISENKO(B, (NwALENTINA kIRIL)QÆWNAs)E; (NgOLOWA]ENKO(B, (NmIHAJLO )QæWANOWI^s)E; (NkRIWO[IJ(B, (NoLEKSANDR pETROWI^s; (NaNDRUS)QÆW(B, (Ns(B.s)E; (NbOGA^EWSXKA(B-(NhOMQK(B, (NmARTA(B,s ((NkI)QÇW (B:s)E (NlIB)QÆDX(B,s)E, 2004)
(NmATER)QÆALI PRO WIDATNIH UKRAÇNOK WÆD ^ASÆW kIÇWSXKOÇ rUSÆ DO NA[IH DNÆWs)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NoLXGAs; (NaNNA qROSLAWNAs; (NgULEWI^ )Qã(B. (Nw(B.s)E; (NmAZEPA m(B.s; )Qã(NFIMENKO o(B. (Nq(B.s)E; (NlITWINOWA(B-(NbARTO[ p(B. (Nq(B.s; (NpOLONSXKA(B-(NwASILENKO n(B. (Nd(B.s; (NrUSOWA s(B. (Nf(B.s; (NgRU[EWSXKA k(B. (Nm(B.s; (NzAGLADA n(B. (Nb(B.s; (N{ULXGINA l(B. (Ns(B.s; (NsPASXKA )Qã(B. (N`(B.s)E; (NdANXK)QÆWSXKA r(B. (Ns(B.s)E; (NtERE]ENKO s(B. (Nm(B.s; (NaPANOWI^ o(B. (Nm(B.s; (NaL^EWSXKA h(B. (Nd(B.s; (NpRIHOTXKO a(B. (Nf(B.s; (NoSAD^A(B-(NqNATA n(B. (Nt(B.s; (NzEROWA m(B. (Nq(B.s; (NpU^KOWSXKA n(B. (No(B.s; (NkAZIMIR^AK(B-(NpOLONSXKA o(B. )Qæ.s)E; (N`]ENKO k(B. (Nl(B.s; (NbELXT@KOWA k(B. (Ng(B.s; (NrUDNICXKA m(B. )Qæ.s)E; (Nm)QÆRNA z(B. (Nw(B.s)E; (NlEW^AN)QÆWSXKAs)E; (NbASARAB o(B. (Nm(B.s; (NsTEPAN)QÆW o(B. æ.s)E; (NmE[KO o(B. (Nq(B.s; (NsUROWCOWA n(B. (Nw(B.s; (NbARW)QÆNOK g(B.s)E; (NwOW^OKs; (NkOBILQNSXKA o(B. (N`(B.s; (NuKRA)QÇNKA l(B.s)E; (Np^)QÆLKAs)E; (NsTARICXKA(B-(N~ERNQH)QÆWSXKA l(B. (Nm(B.s)E; (NgUMENNA d(B. (Nk(B.s; (NtEL)QÆGA o(B. æ.s)E; (NpAWLI^KO s(B. (Nd(B.s; (NbA[KIRCEWA m(B. (Nk(B.s; (NmAZEPA g(B. )Qæ.s)E; (NmOROZOWA l(B.s; (NgORSXKA a(B. (No(B.s; (Nb)QÆLOKUR k(B. (Nw(B.s)E; (NpRIJMA^ENKO m(B.s; (NkRU[ELXNICXKA s(B. (Na(B.s; (NpETRUSENKO o(B. (Na(B.s; (NzARICXKA )Qã(B. (Nr(B.s)E; (NzANXKOWECXKA m(B. (Nk(B.s; (NkORD@M(B-(NoSTROWSXKA l(B. (Nm(B.s; (NsENIK )Qæ(B. (Nm(B.s)E; (NsW)QÆTLI^NA n(B. (No(B.s)E; (Nw)QÆR^ENKO n(B. (No(B.s)E; (Nl)QÆWICXKA(B-(NhOLODNA n(B. (Na(B.s)E; (NkOSTENKO l(B. (Nw(B.s; (NmALAN@K )Qæ(B. (No(B.s)E; (NmATW)QÆÃNKO n(B. (Nm(B.s)E; (NtIM^ENKO m(B. (Nk(B.s; (NkRI^EWSXKA(B-(NrOSANDI^ k(B. (Nw(B.s; (NmAR^ENKO n(B. (Nm(B.s